2021
DOI: 10.3390/medicina57030227
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of EMG-Triggered Robotic Movement on Walking, Muscle Force and Spasticity after an Ischemic Stroke

Abstract: Background and Objectives: Application of the EMG-driven robotic training in everyday therapeutic processes is a modern and innovative form of neurorehabilitation among patients after stroke. Active participation of the patient contributes to significantly higher activation of the sensorimotor network during active motor control rather than during passive movement. The study objective was to determine the effect of electromyographic triggering (EMG-triggered) robotic rehabilitation device treatment on walking,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
2
2
0
2
Order By: Relevance
“…These findings are in agreement with the findings from a previous study by Lewandowska‐Sroka et al. (2021), which examined the effect of conventional versus robotic physiotherapy on thigh circumferences in 60 subjects. In that study, 30 patients were scheduled to undergo five sessions of conventional physiotherapy per week for a duration of 6 weeks.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are in agreement with the findings from a previous study by Lewandowska‐Sroka et al. (2021), which examined the effect of conventional versus robotic physiotherapy on thigh circumferences in 60 subjects. In that study, 30 patients were scheduled to undergo five sessions of conventional physiotherapy per week for a duration of 6 weeks.…”
Section: Discussionsupporting
confidence: 92%
“…However, comparing only between the paretic limbs, the current study showed that the average means of mid-thigh circumferences after 4 weeks of therapy were significantly different between the CR and RR groups. These findings are in agreement with the findings from a previous study by Lewandowska-Sroka et al (2021), which examined the effect of conventional versus robotic physiotherapy on thigh circumferences in 60 subjects. In that study, 30 patients were scheduled to undergo five sessions of conventional physiotherapy per week for a duration of 6 weeks.…”
Section: Discussionsupporting
confidence: 92%
“…Electromyography (EMG) signals have shown potential for detecting muscle state during robotic rehabilitation training in physical therapy. Indeed, rehabilitation robots equipped with reactive electromyography capture EMG signals from a patient’s muscles, allowing them to assist in the rehabilitation process [ 37 ]. Studies have investigated the use of EMG signals in robot-based stroke neurorehabilitation to improve functional outcomes for patients [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ispitanici koji su koristila terapiju bez treninga također su poboljšali motoriku i funkcionalnost (15). U istraživanju s ciljem određivanja učinka liječenja robotskom terapijom pokrenutom EMG signalom korišten je Luna EMG za terapiju gornjih i donjih udova (16). Luna EMG stroj otkriva namjere pokušaja pokreta pacijenta pomoću površinskih EMG signala te pomaže u aktivnostima donjih ekstremiteta, kao savijanje i ispravljanje koljena.…”
Section: Primjena Robota Upravljanih Emg Signalima U Fizioterapiji I ...unclassified